The Alignment of Public Open Space Elements with Visitor Motivation in the Musi Riverfront Public Open Space - Ulfa, Almira; Sri Lilianti Komariah; Fuji Amalia; Rizka Drastiani; Rakhmat Fikran Zuhair (Archvisual: Jurnal Arsitektur dan Perencanaan, 2026)
Public open spaces are considered successful when they are continuously visited and provide tangible benefits to their users. Individuals’ intentions to visit a place, including public open spaces, are driven by internal motivations, whereas the choice of a specific destination is influenced by the elements present within the space. These elements function as pull factors that fulfil visitors’ internal push factors. The Musi River is one of the key images of Palembang City, and several of its riverbanks are utilised as public open spaces consistently visited by the community, including 16 Ilir Market Plaza and Benteng Kuto Besak Plaza. This article examines the elements of public open spaces along the Musi River as pull factors that help fulfil visitors’ push factors in selecting riverfront open spaces as their destination. Data were collected through field observations and the distribution of online questionnaires, and the results were analysed using multivariate correlation analysis. The findings indicate significant relationships between visiting motivations (push factors) and specific elements (pull factors) that are considered essential in public open spaces. In their manifestation as facilities, public open space elements demonstrate a high degree of flexibility, whereby a single element may emerge from the integration of multiple components and derive benefits from the combined elements that constitute it.